Satellite Technologies in Monitoring of Ecosystems (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article provides a description of modern geodetic devices, which are used to solve several problems connected with environmental and hydraulic engineering. In particular, a non-conventional method of area measurement for ecosystems monitoring, which involves the usage of satellite navigation devices, is considered. Nowadays electronic tachymeters, digital levelling instruments, laser scanning systems and satellite systems are widely used for implementation of geodetic engineering works. In full extent it could be also applied to different environmental and hydraulic engineering problems solution.The satellite navigators, especially with GPS+GLONASS system support, are the promising alternative to handle different planimetric tasks, particularly, water surface and drainage area measurement. The paper presents an analysis of the results of research carried out in 2012-2014 years and comparison of them with the new field data. Moreover the obtained results are compared with the theoretical values of quadrates’ areas and the dependence of the relative accuracy versus land plot area is built.Based on a practical research, the accuracy of the method is being estimated. The analysis of different measuring conditions and factors, regarding their effect on accuracy, is made. The suitable areas, where the method could be used, are mentioned. Particularly, the possibility of water surface and drainage area measuring is examined with the usage of previous theoretical base. The paper presents an analysis of the results of research carried out in 2012-2014 years and comparison of them with the new field data. Moreover the obtained results are compared with the theoretical values of quadrates’ areas and the dependence of the relative accuracy versus land plot area is built.Based on a practical research, the accuracy of the method is being estimated. The analysis of different measuring conditions and factors, regarding their effect on accuracy, is made. The suitable areas, where the method could be used, are mentioned. Particularly, the possibility of water surface and drainage area measuring is examined with the usage of previous theoretical base.